In-vitro fertilisation: it's legal standing in Malaysia / Nawal Abdul Aziz, Siti Marfirah Abdullah and Siti Rohiimah Othman - Abdul Aziz, Nawal; Abdullah, Siti Marfirah; Othman, Siti Rohiimah (2008)
The development of technology in medical aspect has contributed to the enhancement of human's life. IVF is one of the creations of technology and it has helped childless couple throughout the world. Thus, question imposed upon this research is that whether Malaysia should solely adopt United Kingdom Human Fertilization and Embryology Act 1990 or whether we should select several relevant sections that applicable. Since Malaysia consists of multi racial and religions, these matters has been taken into consideration in establishing our own law pertaining to IVF. In Malaysia, we have four major religions i.e. Islam, Buddhist, Hindus and Christians. Therefore, opinion from these four religions must be referred first before enacting such law. The research project will set out the Malaysian legal standing of IVF technology and the development of the technology in Malaysia. The fertility centre is mushrooming existed in Malaysia and it shows Malaysian society has accepted the technology as one of the method for childless couple to conceive a children. Moreover, the research project set out (HFEA 1990) as a benchmark of our research due to the absent of similar act in Malaysia. Further, also set out the challenge and obstacle, which Malaysian government faced in enacting the IVF act due to multi racial and religion. As the research project goes along, we had initiate that Malaysia should have it own act pertaining to IVF technology. The absent of the act will causes much difficulties where the practitioners tend to abuse their power in conducting IVF process.